Interlinking of Hypoxia and Estrogen in Thyroid Cancer Progression - Rajoria, S.; Hanly, E.; Nicolini, A.; George, A.L.; Geliebter, J.; Shin, E.J.; Suriano, R.; Carpi, A.; Tiwari, R.K. (Current Medicinal Chemistry, 2014)
Estrogen aids in neo-vascularization of various tumors during hypoxic conditions, however the role of estrogen within the hypoxic environment of thyroid cancer is not known. In a series of experimentations, using human thyroid cancer cells, we observed that estrogen and hypoxia modulate the hypoxia inducible factor-1 (HIF-1) signaling which is abrogated by the anti-estrogen fulvestrant and the HIF-1 inhibitor YC-1 (3-(5’-hydroxymethyl-2’-furyl)-1-benzylindazole). Furthermore, we found that the conditioned medium from estrogen treated thyroid cancer cells lead to enhanced migration and tubulogenesis of human umbilical vein endothelial cells (HUVECs) which is abrogated by HIF-1 inhibitor. These findings, in addition to our previous and other scientific literature data, lead us to conclude that estrogen and hypoxia are interlinked in thyroid cancer and can equally modulate epithelial-endothelial cell interactions by mediating key cellular, metabolic and molecular processes of thyroid cancer progression. We believe that the hormonal component and cellular adaptation to oxygen tension of cancer cells are functionally equivalent with a cellular transition that can be exploited clinically for a combinational approach for thyroid cancer treatment involving antiestrogens as well as anti-hypoxic agents.
Keywords: estrogen